From Brasilia to a Network City: The Reflections of a Russian Sociologist - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2019)
I started my professional activity as the urban planner and researcher in the mid1950s after the visit of Oskar Niemeyer to Moscow. The idea of the article is to trace my own perception and views on various models of an ‘ideal city’ modelling in the context of changing role of large cities in a world social life and the evolution of theories of such cities. Drawing on the study of Russian and foreign literature on urban sociology and planning, on my own theoretical studies and developments and on the participation in three international research projects I came to the following conclusions. First, in the XX and XXI centuries an interest of sociologists and urban planners to the ‘ideal city’ modelling has not been interrupted. Second, there were two main forms of such modelling: the public discussions and pilot projects making. Third, the most impressive international discussion on the future of cities had been conducted in the Soviet Union in the period of 1929-32s. Fourth, before and after the WWII some of the ideas of that discussion had been realized in the process of restoration of Soviet cities. Fifth, with the beginning of so-called Khrushchev era (1950-mid1960s) an urban planning had experienced two major transformations: a regional planning had been quickly developed and an architectural activity had been divided in two realms: the architecture as such and the ‘simple construction.’ Sixth, in parallel the search of an ‘ideal organization’ of everyday life in the form of an ideal neighborhood was continued. Seven, in the end of 1960s we warned our government and professional community that an era of the Fourth Scientific and Technological revolution (hereafter the STR-4) is coming but that appeal had no response. Eighth, only now our scientific and urban community began to realize that we are entering in the transition period toward the construction of our cities on a network basis.